Understanding the Hadith of Blessed Women:: A Ma'na cum MaghzÄ Analysis - Safira Sampe; Miftah Khilmi Hidayatulloh (Prodi Ilmu Hadis Fakultas Ushuluddin dan Dakwah Universitas Islam Negeri Madura, 2026)
The hadith regarding the blessing of women (yumn al-mar'ah) narrated by Imam Ahmad (no. 24478) is often misinterpreted literally, potentially reducing women to objects of biological utility. This study aims to analyze the narration quality and the meaning of the hadith to ensure its relevance for contemporary Muslim society. Employing a literature research design, this study utilizes Mahmud Thahan's takhrij method for sanad analysis and the MaÊ¿nÄ Cum MaghzÄ approach for matan analysis, using primary data from Musnad Ahmad supported by scholarly literature. The results demonstrate that the hadith is á¸¥asan li-Å¼Ätih and elevated to á¹£aá¸¥Ä«á¸¥ li-gairih due to corroborating narrations. Historically, the hadith criticizes social practices that complicate marriage by emphasizing taysÄ«r (ease) in khitbah, dowry, and fertility. Dynamically, the ease of khitbah and dowry underscores fairness, while the concept of the womb has shifted toward a contextual understanding of social and biological benefits. Consequently, the study concludes that the hadith affirms the essential benefits of marriage within the framework of hifáº“ al-dÄ«n, hifáº“ al-nafs, and hifáº“ al-nasl